2017
DOI: 10.5604/01.3001.0010.7037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacteriocin-Producing Lactic Acid Bacteria Isolated from Native Fruits of Ecuadorian Amazon

Abstract: Tropical, wild-type fruits are considered biodiverse "hotspots" of microorganisms with possible functional characteristics to be investigated. In this study, several native lactic acid bacteria (LAB) of Ecuadorian Amazon showing highly inhibitory potential were identified and characterized. Based on carbohydrate fermentation profile and 16S rRNA gene sequencing, seven strains were assigned as Lactobacillus plantarum and one strain as Weissella confusa. Using agar-well diffusion method the active synthetized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…No significant difference (p > 0.05) was observed between the Cys5-4, LP and nitrite upon 9 days of storage. ese results were in agreement with our previous findings that Cys5-4 inhibited in vitro the growth of E. coli and Salmonella at both vegetative and exponential target growth [13]. ese results are similar to the results obtained using the crude extract of Lactobacillus LAC231 on the microbiota presented in the meat packed in controlled atmospheres [19].…”
Section: Bacteriocins Produced By Cys5-4 Reduced the Viability Of Micsupporting
confidence: 92%
See 4 more Smart Citations
“…No significant difference (p > 0.05) was observed between the Cys5-4, LP and nitrite upon 9 days of storage. ese results were in agreement with our previous findings that Cys5-4 inhibited in vitro the growth of E. coli and Salmonella at both vegetative and exponential target growth [13]. ese results are similar to the results obtained using the crude extract of Lactobacillus LAC231 on the microbiota presented in the meat packed in controlled atmospheres [19].…”
Section: Bacteriocins Produced By Cys5-4 Reduced the Viability Of Micsupporting
confidence: 92%
“…is observation is consistent with our previous findings about the bactericidal mode of action of the bacteriocin Cys5-4 [13]. In a recent paper, the molecular weight of partial purified bacteriocin from L. plantarum ATCC8014 was estimated at 68 kDa [30], while a previous study indicated that the protein was larger than 122 kDa [31].…”
Section: Bacteriocin Cys5-4 Induced Killing By Disrupting the Cellsupporting
confidence: 92%
See 3 more Smart Citations